Product feedback regulation implicated in translational control of the Trypanosoma brucei S‐adenosylmethionine decarboxylase regulatory subunit prozyme. Issue 5 (2nd May 2013) - Xiao, Yanjing; Nguyen, Suong; Kim, Sok Ho; Volkov, Oleg A.; Tu, Benjamin P.; Phillips, Margaret A.
Summary Human African sleeping sickness (HAT) is caused by the parasitic protozoan Trypanosoma brucei. Polyamine biosynthesis is an important drug target in the treatment of HAT. Previously we showed that trypanosomatid S‐adenosylmethionine decarboxylase (AdoMetDC), a key enzyme for biosynthesis of the polyamine spermidine, is activated by heterodimer formation with an inactive paralogue termed prozyme. Furthermore, prozyme protein levels were regulated in response to reduced AdoMetDC activity. Herein we show that T. brucei encodes three prozyme transcripts. The 3′UTRs of these transcripts were mapped and chloramphenicol acetyltransferase (CAT) reporter constructs were used to identify a 1.2 kb region that contained a 3′UTR prozyme regulatory element sufficient to upregulate CAT protein levels (but not RNA) upon AdoMetDC inhibition, supporting the hypothesis that prozyme expression is regulated translationally. To gain insight into trans‐acting factors, genetic rescue of AdoMetDC RNAi knock‐down lines with human AdoMetDC was performed leading to rescue of the cell growth block, and restoration of prozyme protein to wild‐type levels. Metabolite analysis showed that prozyme protein levels were inversely proportional to intracellular levels of decarboxylated AdoMet (dcAdoMet). These data suggest that prozyme translation may be regulated by dcAdoMet, a metabolite not previously identified to play a regulatory role.